The association between dental mineralization and mandibular form: a study combining additive conjoint measurement and geometric morphometrics. - Coquerelle, Michael; Bayle, Priscilla; Bookstein, Fred L; Braga, José; Halazonetis, Demetrios J; Katina, Stanislav; Weber, Gerhard W (J Anthropol Sci, 2010)
Studies have suggested that dental development substantially influences the variation of mandibular morphology and growth in primates. As a contribution to the methodology of such studies, we introduce a novel approach to quantifying the covariation between teeth and mandible. This was done showing fluctuations in the magnitude of this covariation within a sample of modern human mandibles at different postnatal ages. Dense CT- derived mandibular surface meshes of 73 females and 71 males, ranging in age from birth to adulthood, were processed by methods of geometric morphometrics. Each specimen's deciduous and permanent teeth were rated for mineralization stage. Form-space principal component analysis of the morphometric data was used to produce a single metric variable that best explains mandibular-form variation. This variable was then used to quantify the developing teeth, all together, through the use of the additive conjoint measurement method. This new metric variable corresponds to the dental prediction of the mandibular-form variation. Finally, we examine the covariation of the two over the full range of mineralization stages. We found a strikingly tight association between mandibular form and dental maturation up through the full emergence of the deciduous dentition (about age 2 years), followed by an equally striking decline in that association in later developmental stages, particularly for girls. The onset of the decline of the teeth-mandible relationship coincides with the onset time of the adult-like pattern of mastication and speech. The increasingly functional diversity may lead to more independence between dental development and mandibular growth than during the first two years.
Keywords: Adolescent; Adult; Aging; Anthropometry; Child; Child, Preschool; Dentition, Permanent; Female; Humans; Infant; Infant, Newborn; Male; Mandible; Tooth; Tooth, Deciduous; Young Adult